2004
DOI: 10.1523/jneurosci.3234-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Genomic Changes in the Mouse Ocular Motor System in Response to Light Deprivation from Birth

Abstract: Previous studies have suggested that abnormal visual experience early in life induces ocular motor abnormalities. The purpose of this study was to determine how visual deprivation alters the function and gene expression profile of the ocular motor system in mice. We measured the effect of dark rearing on eye movements, gene expression in the oculomotor nucleus, and contractility of isolated extraocular muscles. In vivo eye movement recordings showed decreased gains for optokinetic and vestibulo-ocular reflexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 69 publications
3
20
0
Order By: Relevance
“…In addition to employing pulse stimuli along the lines used in the previous study of electrical stimulation in the primate (Anderson et al 2009), we also explored the potential to use sinusoidal optogenetic stimuli to characterize ocular motor mechanics. Finally, we examined the degree to which a dependence of time constants on stimulus duration is a property of the muscles themselves, based on data from activation of isolated extraocular muscles in vitro generated for a previously published study (McMullen et al 2004).…”
mentioning
confidence: 99%
“…In addition to employing pulse stimuli along the lines used in the previous study of electrical stimulation in the primate (Anderson et al 2009), we also explored the potential to use sinusoidal optogenetic stimuli to characterize ocular motor mechanics. Finally, we examined the degree to which a dependence of time constants on stimulus duration is a property of the muscles themselves, based on data from activation of isolated extraocular muscles in vitro generated for a previously published study (McMullen et al 2004).…”
mentioning
confidence: 99%
“…Although several studies have already examined contractile properties of mouse extraocular muscles (McMullen et al 2004;Yin et al 2005;Zhou et al 2009), other aspects of the ocular motor plant mechanics have yet to be explored, in particular the transformation between motoneuron firing and eye movement. A description of this relationship is an important precursor to exploring signal processing within the murine vestibular, optokinetic, and ocular motor circuits as discussed above.…”
mentioning
confidence: 99%
“…More recently it has been shown that visual deprivation can lead to IN-like oscillations in monkey (Tusa et al, 2001). The plausibility of this is further ramified by the demonstration that cascades of gene expressions can be affected by early visual deprivation in the (afoveate) mouse (McCullen et al, 2004), which not only blurs the naturenurture division, but provides a rather daunting preview into the complexity of genetic control of normal and abnormal visuomotor development. The companion of complexity is vulnerability to error, and the question arises how control is maintained in spite of genetic polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of this synchonization through delayed sensory development in the presence of normal motor development, or precocious oculomotor development in the presence of normal sensory development, would then lead to IN. Recent studies in mice have shown that early visual deprivation can lead to a whole cascade of changes in gene expressions for extraocular muscle, oculomotor systems (delayed OKN & VOR) and neural plasticity (McCullen et al, 2004). It is likely that there is a similar genetic control of foveal development and plasticity in the eye movement systems that support foveal function (gaze holding, smooth pursuit, fast OKN).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation